Subchronic effects of fluoxetine on conditioned suppression produced by a hot air blast - Nascimento,Gabriela Souza do (2012)
Conditioned suppression is an animal model of anxiety disorders that has been broadly used to investigate the behavioral effects of different drugs. However, various methodological variables (e.g., the type of aversive stimulus) that supposedly interfere with the acquisition of conditioned suppression may also contribute to conflicting results among the studied drugs. Additionally, few studies have sought to investigate the effects of selective serotonin reuptake inhibitors (SSRIs). The present study investigated the effect of subchronic 5-day administration of 5 mg/kg fluoxetine in the retention of conditioned suppression produced by a hot air blast (HAB). The subjects were 12 albino Wistar rats distributed into an Experimental Group (EG) and Control Group (CG). After sessions were conducted to pair two stimuli, a sound and HAB, fluoxetine (EG) or saline (CG) was administered. Twenty-four hours after the last injection, a test session was conducted. The results showed no difference between groups. Fluoxetine (5 mg/kg) did not exert anxiolytic effects in this model of conditioned suppression produced by a HAB.